Computerized nursing process in the Intensive Care Unit: ergonomics and usability - Sônia Regina Wagner de Almeida; Grace Teresinha Marcon Dal Sasso; Daniela Couto Carvalho Barra
Abstract OBJECTIVE Analyzing the ergonomics and usability criteria of the Computerized Nursing Process based on the International Classification for Nursing Practice in the Intensive Care Unit according to International Organization for Standardization(ISO). METHOD A quantitative, quasi-experimental, before-and-after study with a sample of 16 participants performed in an Intensive Care Unit. Data collection was performed through the application of five simulated clinical cases and an evaluation instrument. Data analysis was performed by descriptive and inferential statistics. RESULTS The organization, content and technical criteria were considered "excellent", and the interface criteria were considered "very good", obtaining means of 4.54, 4.60, 4.64 and 4.39, respectively. The analyzed standards obtained means above 4.0, being considered "very good" by the participants. CONCLUSION The Computerized Nursing Processmet ergonomic and usability standards according to the standards set by ISO. This technology supports nurses' clinical decision-making by providing complete and up-to-date content for Nursing practice in the Intensive Care Unit.